Meningkatkan Kemampuan Belajar IPA Mengenal Rangka Manusia dengan Model Pembelajaran Contextual Teaching and Learning Pada Anak Tunagrahita Ringan - Jonni Lastua Sitorus; Zulmiyetri Zulmiyetri (Jurnal Penelitian Pendidikan Khusus, 2023)
This research was carried out at the Batu Bara State Special School in Medan with the aim of increasing the ability to learn science about the human skeleton in class XI mild mentally retarded children. The subjects of this study were the teacher of class XI mild intellectual disability at Batu Bara State Special School and two mild mentally retarded students who studied in class XI of Batu Bara State Special School. This research is a classroom action research conducted using the Contextual Teaching and Learning learning model for students which is carried out in two research cycles, each cycle is carried out in four meetings. The results of the actions given by the teacher to students in the first cycle for each child are HS students in the first meeting the child has the ability as much as 31%, the second meeting 38%, the third 50% and the fourth 63%. While the WS students at the first meeting were 38%, second 50%, third 63% and fourth 75%. While the results achieved by students in the second cycle were at the first meeting the HS students reached 69%, the second 69%, the third 75%, and the fourth, 81 percent, while for the WS students at the first meeting, the second 81%, the third 75%, 88% and the fourth 88%. . Based on these results, it can be concluded that the Contextual Teaching and Learning learning model is effective in improving science learning abilities to recognize the human skeleton in mild mentally retarded children at SLB Negeri Batu Bara Medan.